2022
DOI: 10.3390/md20060370
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin Is a Potential Therapeutic Agent for the Treatment of Breast Cancer

Abstract: Breast cancer (BC) is one of the most common cancers diagnosed and the leading cause of cancer-related death in women. Although there are first-line treatments for BC, drug resistances and adverse events have been reported. Given the incidence of BC keeps increasing, seeking novel therapeutics is urgently needed. Fucoxanthin (Fx) is a dietary carotenoid commonly found in seaweeds and diatoms. Both in vitro and in vivo studies show that Fx and its deacetylated metabolite fucoxanthinol (Fxol) inhibit and prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 254 publications
0
11
0
Order By: Relevance
“…Studies show that fucoxanthin significantly reduced VEGF-C, VEGFR-3, NF-κB, phospho-Akt, and phospho-PI3K in HLEC in breast cancer [121]. Moreover, data showed that fucoxanthin inhibited mRNA expression of VEGF-C in MDA-MB-231 cells [121,186].…”
Section: The Effect Of Fucoxanthin On Cytokines Formation and Releasementioning
confidence: 96%
“…Studies show that fucoxanthin significantly reduced VEGF-C, VEGFR-3, NF-κB, phospho-Akt, and phospho-PI3K in HLEC in breast cancer [121]. Moreover, data showed that fucoxanthin inhibited mRNA expression of VEGF-C in MDA-MB-231 cells [121,186].…”
Section: The Effect Of Fucoxanthin On Cytokines Formation and Releasementioning
confidence: 96%
“…338,339 Only one rst total synthesis of a brown algal MNP was reported in 2022, that of carotenoid loroxanthin. 340 Reviews focusing on brown algae and their metabolites published in 2022 include summaries of the anticancer activity of various eckols and fucoxanthin, respectively, 341,342 phlorotannins as sedative aids for promoting sleep, 343 and catalogues of the compounds found from species Ecklonia stolonifera, 344 and the genera Dictyota and Dictyopteris, respectively. 345,346 An in silico study of various brown algal phlorotannins as SARS-COV-2 protease inhibitors identied several lead compounds, which were then validated as weak to moderate inhibitors using in vitro bioassays.…”
Section: Brown Algaementioning
confidence: 99%
“…Carotenoids are natural pigments that have received particular attention because of their ecophysiological function, biotechnological applications, and their potential beneficial effects on human health [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The color of these molecules can range from colorless to red, through various yellow-orange tones, and they represent the second most abundant natural pigments in nature [ 45 , 46 ].…”
Section: Archaea Pigments: Bacteriorhodopsin and Carotenoidsmentioning
confidence: 99%
“…Animals, including humans, consume phototrophic organisms and utilize carotenoids or apocarotenoids for important physiological functions, including body coloration, sexual attractiveness, vitamin A production, antioxidant activity, transcription factor activation and photoreception. Pharmacological studies have also demonstrated the diverse biological activities of carotenoids and apocarotenoids, including antimicrobial, antifungal, antidiabetic, immunostimulant, anti-obesity, anti-inflammatory, anticarcinogenic and cancer-preventive, antimetastatic, antiangiogenic, radioprotective, anti-atherosclerotic, neuroprotective and chemosensitizing properties of multidrug-resistant cancer cells [ 37 , 39 , 41 , 43 , 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]…”
Section: Archaea Pigments: Bacteriorhodopsin and Carotenoidsmentioning
confidence: 99%